Disability and Work: The United Republic of Tanzania's Workplace Policies in the Persons with Disabilities Act of 2010 - Aldersey, Heather (Disability Studies Quarterly, 2012)
Nations are increasingly demonstrating a commitment to disability rights by enacting national policies on disability. Among them, the United Republic of Tanzania has, in addition to being a signatory to the United Nations Convention on the Rights of Persons with Disabilities (CRPD), made a public commitment to the rights of persons with disabilities through a number of national policy mechanisms such as the Persons with Disabilities Act of 2010. As in other nations with policy commitments to disability rights, however, the principles and promises made in policy documents often are not reflected in direct action for the Act’s intended beneficiaries. This article explores the challenges of translating policy to action by examining the accountability mechanisms tied to the employment-related Articles of the Persons with Disabilities Act of 2010 and by discussing studies that provide the "on the ground" employment reality in Dar es Salaam, Tanzania. Keywords: Tanzania, Policy, People with Disabilities Act, Workplace Quotas, Employment